The clinical impact of ST131 H30-Rx subclone in urinary tract infections due to multidrug-resistant Escherichia coli. (March 2016) - Can, Fusun; Kurt-Azap, Özlem; İspir, Pelin and Nurtop, Elif and Seref, Ceren and Loçlar, İlayda and Aktaş, Ozge Nur and Orhan, Yelda Ceren and Ergonul, Onder
Highlights: Approximately 20% of multidrug-resistant (MDR) isolates were H30-Rx subclone. Urinary MDR Escherichia coli ST131 H30-Rx subclone was found to be important in dissemination of MDR UTIs in the community. Infection with this subclone was found to be healthcare-associated. Abstract: In this study, risk factors for ST131 H30 and H30-Rx subclones among urinary tract infections (UTIs) caused by multidrug-resistant (MDR) Escherichia coli were described. Urine samples were collected from consecutive outpatients registered to the outpatient clinics of Başkent University Hospital (Ankara, Turkey) with complaints of acute cystitis in 2011. A total of 107 MDR E. coli isolates were included in the study. Of the 107 isolates studied, 26 (24.3%) were typed as ST131 clone. Extended-spectrum β-lactamase (ESBL)-producers accounted for 59 (55.1%) of the 107 isolates. Among the 59 ESBL-positive isolates, 18 (31%) were found to belong to the ST131 clone. Of the 18 ESBL-positive ST131 isolates, 17 (94%) were defined as H30 subclone, among which 16 (94%) represented the H30-Rx subclone. Among the 48 ESBL-negative isolates, 8 (17%) ST131 isolates were detected, 7 (88%) of which belonged to H30 subclone; 5 (71%) of the H30 subclone isolates were classified under H30-Rx subclone. In multivariate analysis, hospitalisation within last year was the only host risk factor associated with MDR E. coli ST131 H30-Rx subclone UTI (OR = 3.5, 95% CI 1.04–12.17; P = 0.042). CTX-M-15 production was found to be highly associated with the presence of ST131 H30-Rx subclone (OR = 4.8, 95% CI 1.54–15.32; P = 0.007). In conclusion, urinary MDR E. coli ST131 H30-Rx subclone was found to be important in the dissemination of MDR UTIs in the community. Approximately 20% of the MDR isolates were H30-Rx subclone. Infection with this subclone was found to be healthcare-associated.